TEACHERS’ USE OF TIERED LESSONS AS A DIFFERENTIATED INSTRUCTION STRATEGY: A MULTIPLE-CASE STUDY OF THREE PRIMARY EFL CLASSROOMS = VIỆC SỬ DỤNG TIẾT HỌC PHÂN TẦNG NHƯ MỘT CHIẾN THUẬT DẠY HỌC PHÂN HÓA: MỘT NGHIÊN CỨU ĐA ĐIỂN HÌNH TẠI BA LỚP TIẾNG ANH TIỂU HỌC - Phạm, Phương Anh (2020)
Much as individual uniqueness is honoured, it has been a challenge for teachers and educators to cater for learner diversity in their classrooms. Differentiated instruction is a conceptual approach that offers teachers viable solutions to address this academic diversity. One such solution is the use of tiered lessons, which allows for individual students’ optimum growth and varied modalities of accomplishments. Despite its proven effectiveness, there has been little attention paid to this pedagogical strategy in Vietnamese EFL teaching context. To bridge that gap, this qualitative case study aims to investigate teachers’ use of tiered lessons as a differentiated instruction strategy in three primary EFL classes. Three research questions of this study focused on the implementation of tiered lessons, its successes and challenges, together with professional preparations for a successful differentiated classroom. To answer these questions, a multiple-case study was selected as research design and the participants in this study were two native English-speaking teachers. The data collected from documents, interviews and observations was coded for emerging themes using thematic analysis. The findings revealed that the teachers incorporated tiered lessons in their teaching by establishing positive learning environment, giving adaptive instruction, and assessing students accordingly. In addition, students’ academic growth and increased engagement were the perceived successes while the challenges remained in the teachers’ understanding and their daily implementation of tiered lessons. It was recommended that consistent professional development and teachers’ collaborative planning were the necessary preparation for the deployment of tiered lessons.